2021
DOI: 10.1371/journal.pone.0244885
|View full text |Cite
|
Sign up to set email alerts
|

A novel aqueous extract from rice fermented with Aspergillus oryzae and Saccharomyces cerevisiae possesses an anti-influenza A virus activity

Abstract: Human influenza virus infections occur annually worldwide and are associated with high morbidity and mortality. Hence, development of novel anti-influenza drugs is urgently required. Rice Power® extract developed by the Yushin Brewer Co. Ltd. is a novel aqueous extract of rice obtained via saccharization and fermentation with various microorganisms, such as Aspergillus oryzae, yeast [such as Saccharomyces cerevisiae], and lactic acid bacteria, possessing various biological and pharmacological properties. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Viral titers were determined by immunostaining of the influenza A viral nucleoprotein, as previously described. [16][17][18] through NB staining and MTT assay. NB staining was conducted as described previously 19) , and viable cells in each well were stained blue, whereas dead cells were unstained.…”
Section: Strains Of Influenza a Virusmentioning
confidence: 99%
“…Viral titers were determined by immunostaining of the influenza A viral nucleoprotein, as previously described. [16][17][18] through NB staining and MTT assay. NB staining was conducted as described previously 19) , and viable cells in each well were stained blue, whereas dead cells were unstained.…”
Section: Strains Of Influenza a Virusmentioning
confidence: 99%
“…FR extracts prevent NaCl or methotrexate cytotoxicity in the gastric mucosa ( Ochiai et al, 2013 ), enhance antioxidant activity ( Shin et al, 2019 , Xu et al, 2019 ), have anti-inflammatory efficacy in the intestinal mucosa ( Oh et al, 2020 ), lower blood and hepatic cholesterol levels, and exhibit anti-steatosis activity ( Bunnoy et al, 2015 ). Rice extracts fermented with Aspergillus oryzae and/or Saccharomyces cerevisiae ( S. cerevisiae ) may be administered as anti-influenza therapy and are sources of anti-influenza drugs ( Shoji et al, 2021 ). S. cerevisiae -based fermentation contains abundant β-glucans which improve intestinal health and increase post-vaccination antibody titers in poultry ( Dewi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that gavage of glutinous rice-fermented yellow wine to constipated mice can modulate microbiota-mediated intestinal ecology, regulate intestinal and serum metabolite levels, and increase gastrointestinal motility, exerting a therapeutic effect on constipation [ 8 ]. In addition, rice extracts fermented by Aspergillus oryzae have also been found to be a source of anti-influenza drugs and drugs for the development of anti-influenza compounds [ 9 ]. D. officinale is a medicinal and food plant containing a variety of bioactive components, such as polysaccharides, biphenyls, phenanthrenes, and flavonoids.…”
Section: Introductionmentioning
confidence: 99%